2021
DOI: 10.1108/he-09-2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

Successful health-promoting leadership – A question of synchronisation

Abstract: PurposeThe aim of this paper is to identify the role of the principal in establishing a whole school approach for health and wellbeing. Two questions are asked: (1) What do successful Swedish principals do when they take on a whole school approach? (2) How do these results relate to previous research on successful school leadership?Design/methodology/approachThis paper focuses on the complexity of organisational processes and considers the role of successful leadership in managing a whole school approach to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, this responsibility was only devolved to other staff members because school leaders viewed PE as an additional burden in an already overcrowded curriculum. In Sweden, Skott (2021) reported that schools showed remarkable progress in health-promoting activities when principals supported work using a distributed leadership approach. In contrast, Viig et al (2012) found that a top-down approach was regarded as effective in the development and implementation of school health promotion by programme leaders in Norway, as this way, teachers gave it greater priority, and school leaders had the authority to allocate time and resources.…”
Section: Shared Leadership Approachesmentioning
confidence: 99%
“…However, this responsibility was only devolved to other staff members because school leaders viewed PE as an additional burden in an already overcrowded curriculum. In Sweden, Skott (2021) reported that schools showed remarkable progress in health-promoting activities when principals supported work using a distributed leadership approach. In contrast, Viig et al (2012) found that a top-down approach was regarded as effective in the development and implementation of school health promotion by programme leaders in Norway, as this way, teachers gave it greater priority, and school leaders had the authority to allocate time and resources.…”
Section: Shared Leadership Approachesmentioning
confidence: 99%
“…However, the implementation and maintenance of HPS are complex, as different actors, contents, and levels must be considered. Therefore, leadership and the coordination of such processes are essential [ 21 , 22 , 23 , 24 ]. Studies show that school leaders act as gatekeepers for health promotion and, thus, decisively influence schools’ prevention and health-promotion activities [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that school leaders act as gatekeepers for health promotion and, thus, decisively influence schools’ prevention and health-promotion activities [ 25 , 26 ]. School leaders not only initiate health-promoting activities, but also continuously accompany the health-promotion actions of their schools by handling motivational, organizational, and content-related aspects, and integrating health promotion into daily practice [ 13 , 24 ]. The significance of school leaders in health promotion is also identified by Zumbrunn et al and Gieske and Harzd [ 16 , 27 ] who ascribe a central role to school leaders in ensuring and coordinating health-promotion activities in their schools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPL enhances the health of subordinates in several ways. First, HPL is integral to developing health-promoting environments (Skott, 2022), which may lead to enhanced teacher performance, commitment and satisfaction. Second, leaders may also change working conditions by creating a supportive working atmosphere and nourishing resources that foster employee health (Bregenzer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%